State reform, democracy and multiethnic citizenship: The recognition of legal pluralism - Cabedo Mallol, Vicente José (2002)
The reform of the States in Latin America responds to the dynamics of what has come to be called the "double transition"; on the one hand, towards neoliberalism or, if you prefer, towards the globalized economy, and, on the other, towards democracy. In this way, as Willem Assies points out, "while on the one hand the constitutional and State reforms respond to the demands and guidelines of the multilateral mechanisms, on the other hand they cannot fail to take into account certain expectations of the local population generated in the framework of the processes of “democratic transition.” Precisely, in this framework of transition to democracy, the States recognize the ethnic and cultural diversity present in their territories.